Implementasi Akad Mudharabah dan Musyarakah pada Teknologi Finansial Syariah dengan Pendekatan Kemaslahatan - Suhardi Kamaruddin (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2022)
This study uses a combination of literature and field research with qualitative methods carried out by descriptive analysis. Data collection methods include interviews, observations, and documentation which are then analyzed through several stages: data reduction, data presentation, and conclusion drawing. The results of the study revealed that: (1) Mudharabah contract financing conducted by Sharia Fintech Ammana in accordance with the basic concept of mudharabah transactions, as stipulated in the DSN-MUI fatwa No. 117/DSN-MUI/II/2018, then the Financing Musyarakah contract run by Ammana Fintech Syariah is in line with the basic concept of the Musyarakah transaction as the provisions of the DSN fatwa No.117/DSN-MUI/II/2018. From the analysis of the implementation of the mudharabah and musyarakah contracts, it is very relevant to the principles of Islamic economics. (2) The concept of maslahah in mudharabah and musyarakah contracts in improving the community's economy, SMEs the provide a very solution. and includes elements of mashlahah such as guarding religion, guarding the soul, guarding reason, guarding property, and guarding offspring. The results of the analysis obtained in terms of customer financing at Ammana Fintek Syariah obtain business development for SMEs.